2016
DOI: 10.1371/journal.pone.0168765
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Inhibits Platelet-Derived Growth Factor-Driven Cell Proliferation via Downregulation of N-Glycosylation in Human Tenon's Fibroblasts in a Proteasome-Dependent Manner

Abstract: The objective of this study was to evaluate the effects of silibinin on cell proliferation in platelet-derived growth factor (PDGF)-treated human Tenon's fibroblasts (HTFs). The effect of silibinin on cell proliferation in PDGF-treated HTFs was determined by examining the expression of proliferating cell nuclear antigen (PCNA) and performing WST-1 assays. Cell cycle progression was evaluated using flow cytometry. The related cyclins and cyclin-dependent kinases (CDKs) were also analyzed using western blot. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In contrast to FGF and VEGF, PDGF-BB amounts, however, were found to be significantly lower in supernatants of tri-cultures containing the fibroblast cell line SV80. PDGF-BB is known as a major driver of fibroblast growth and regeneration and thus was consumed by SV80 cells during microtissue formation 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to FGF and VEGF, PDGF-BB amounts, however, were found to be significantly lower in supernatants of tri-cultures containing the fibroblast cell line SV80. PDGF-BB is known as a major driver of fibroblast growth and regeneration and thus was consumed by SV80 cells during microtissue formation 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…There are few papers regarding the effect of sylibins on proteasome activity. Some biochemical assays have demonstrated that silibinin may inhibit Platelet-Derived Growth Factor-Driven (PDGF) cell proliferation in human fibroblasts by enhancing the UPS activity, albeit information about a direct silibyn/proteasome interactions is largely incomplete . Silibinin is also known as an effective autophagy enhancer, since as silibinin treatment rescued glucose metabolism in streptozotocin-induced diabetic mice …”
Section: Rescuing Iapp Proteostasis By Small Moleculesmentioning
confidence: 99%
“…It was found that silibinin had the ability to downregulate PDFG in fibroblasts, thus decreasing proliferation. 194 Silymarin Decreases the Levels of Interleukin 8 (IL-8)…”
Section: Silymarin and Phospholipase A2mentioning
confidence: 99%